Untargeted metabolomic analysis of the carotenoid-based orange coloration in Haliotis gigantea using GC-TOF-MS - Xiaohui Wei (Nature Portfolio, 2019)
Abstract Seafood coloration is typically considered an indicator of quality and nutritional value by consumers. One such seafood is the Xishi abalone (Haliotis gigantea), which displays muscle color polymorphism wherein a small subset of individuals display orange coloration of muscles due to carotenoid enrichment. However, the metabolic basis for carotenoid accumulation has not been thoroughly investigated in marine mollusks. Here, GC-TOF-MS-based untargeted metabolite profiling was used to identify key pathways and metabolites involved in differential carotenoid accumulation in abalones with variable carotenoid contents. Cholesterol was the most statistically significant metabolite that differentiated abalones with orange muscles against those with common white muscles. This observation is likely due to the competitive interactions between cholesterol and carotenoids during cellular absorption. In addition, the accumulation of carotenoids was also related to fatty acid contents. Overall, this study indicates that metabolomics can reflect physiological changes in organisms and provides a useful framework for exploring the mechanisms underlying carotenoid accumulation in abalone types.